Consolidation works on sandstone monuments: A new approach - Ludovico-Marques, Marco (2019)
Abstract Sandstones are widely used in the building elements of the world’s stone monuments. Alveolization due to salt crystallization-dissolution is the most important degradation pattern found on the Middle Ages’ sandstone façades of St. Leonardo’s Church in Portugal. An outstanding case of widespread distribution of deep and large alveolization patterns found mainly on portals and vaults of its sandstone façades appeared as a result of the past and present proximity of the seashore. On stonewall façades, a new approach of consolidating products’ treatments using the total head was followed in order to allow full absorption of stone. Physical and mechanical tests were carried out on selected representative specimens of varieties of sandstones on the monument. Treatments with ethyl silicates were assessed by means of its effectiveness, harmfulness, and durability. The comparison of results between the application of this new procedure on this stone monument and the traditional intervention treatments highlighted the potential viability of the former to overcome difficult conditions of absorption of consolidating products.